Modulation of substance P signaling by dipeptidyl peptidase-IV enzymatic activity in human glioma cell lines - Busek, P; Stremeňová, J; Krepela, E; Sedo, A (Physiological research, 2008)
Dipeptidyl peptidase-IV (DPP-IV, CD26) is a serine protease almost ubiquitously expressed on cell surface and present in body fluids. DPP-IV has been suggested to proteolytically modify a number of biologically active peptides including substance P (SP) and the chemokine stromal cell derived factor-1alpha (SDF-1alpha, CXCL12). SP and SDF-1alpha have been implicated in the regulation of multiple biological processes and also induce responses that may be relevant for glioma progression. Both SP and SDF-1alpha are signaling through cell surface receptors and use intracellular calcium as a second messenger. The effect of DPP-IV on intracellular calcium mobilization mediated by SP and SDF-1alpha was monitored in suspension of wild type U373 and DPP-IV transfected U373DPPIV glioma cells using indicator FURA-2. Nanomolar concentrations of SP triggered a transient dose dependent increase in intracellular calcium rendering the cells refractory to repeated stimulation, while SDF-1 had no measurable effect. SP signaling in DPP-IV overexpressing U373DPPIV cells was not substantially different from that in wild type cells. However, preincubation of SP with the DPP-IV overexpressing cells lead to the loss of its signaling potential, which could be prevented with DPP-IV inhibitors. Taken together, DPP-IV may proteolytically inactivate local mediators involved in gliomagenesis.
Keywords: vápníková signalizace; mifepriston; Dipeptidyl Peptidase 4; Mifepristone; inhibitory dipeptidylpeptidasy 4; Oligopeptides; Calcium Signaling; U937 buňky; Humans; Chemokine CXCL12; U937 Cells; dipeptidylpeptidasa 4; gliom; Dipeptidyl-Peptidase IV Inhibitors; inhibitory serinových proteinas; Pyrrolidines; substance P; Substance P; Lysine; chemokin CXCL12; Serine Proteinase Inhibitors; pyrrolidiny; lysin; Brain Neoplasms; transfekce; nádory mozku; lidé; oligopeptidy; Glioma; Transfection